Partial vertebrectomy with spine shortening for old spondyloptosis at the thoracolumbar spine: a case series study and literature review - Nuo Xu; Ping Liu; Yijun Kang; Fei Chen (Frontiers in Surgery, 2023)
ObjectiveWe aimed to report the surgical outcomes of serial cases and retrospectively analyze the value of partial vertebrectomy and spinal shortening in the reduction of old spondyloptosis at the thoracolumbar spine.MethodsFrom 2015 to 2021, eight cases of patients who received a spinal intervention of partial vertebrectomy and spinal shortening for thoracolumbar spondyloptosis over 3 weeks post-trauma were retrospectively summarized. Medical records and surgical outcomes were extracted for clinical safety and efficacy evaluation.ResultsAcceptable reduction and immediate stabilization were achieved for all eight cases without causing iatrogenic damage to the viscera. The mean operation time was 3.7 h (range, 3.2–4.2 h) with a mean blood loss average of 1,081 ml (range, 900–1,300 ml). Postoperative stay in the spine department was an average of 11.4 days (range, 8–17 days), followed by an early rehab program. The mean visual analog scale (VAS) for low back pain decreased from 8.0 preoperatively to 1.4 at the last follow-up. The average follow-up period was 19.9 months. As for neurological function recovery, six patients with preoperative ASIA-A status remained unchanged throughout the follow-up period and improvement of one ASIA grade was noted in two patients. At the latest follow-up, sound interbody fusion as well as good alignment of the spinal column were confirmed radiologically in seven patients, while one patient encountered slight re-dislocation 3 months after surgery, but eventually achieved spinal fusion.ConclusionPartial vertebrectomy and spine shortening via a posterior approach showed good efficacy and safety in the management of old spondyloptosis of the thoracolumbar spine, allowing for a one-step good reduction and spinal fusion for early rehabilitation.